Tantangan Etika di Bidang Perhotelan pada Era Artificial Intelligence - Yuli Arisanti (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The use of AI (artificial intelligence) has penetrated the hospitality sector, thereby requiring ethical guidelines. Research to explain ethical challenges in the hospitality sector. The research was carried out using the literature study method. The research results show that ethical challenges are fairness, reliability, security, privacy, security, inclusiveness, transparency and accountability. Ethics in non-technical fields such as employee reduction issues, employee dedication. The hotel industry needs to understand ethics in both technical and non-technical fields. Criteria for leaders needed in the AI era in the hospitality sector who have ACKEH (Agile, Communication, Knowledge, Ethics, Empathy, and Hospitality) skills. This research provides solutions to face AI ethical challenges and enriches literacy in the field.